Analysis Kualitas Handle Seat Track Adjuster Menggunakan Metode Six Sigma dengan Pendekatan Dmaic di PT XYZ - Muhamad Linsyi Daissurur; Fibi Eko Putra; Agus Andriyansyah (Yayasan Literasi Sains Indonesia, 2026)
PT XYZ is a manufacturing industry that operates in the field of automotive component production, especially handle seat track adjuster which functions as a part for adjusting the position of the seat of a four-wheeled vehicle. The problem faced by the company is the high level of product defects due to the manufacturing process stamping and bending which is not yet optimal. There are three types defect the main thing is burry, not enough bending, and the material expands, with defect burry as the largest contributor, reaching 370 units out of a total production of 20,700 units. From October to December, the highest product defect rate occurred in December, with a percentage of 3.84%. This study aims to analyze and propose improvements to reduce the defect rate using the Six Sigma method with the DMAIC approach (Define, Measure, Analyze, Improve, Control). Analysis using Pareto diagrams and fishbone diagram shows that the main cause defect derived from machine, method, material, and human factors. The results of the study show an average value defect of 2.85% with a DPMO of 9,530.42 and a sigma level of 3.87. The proposed improvements are focused on maintenance dies, standardization of machine parameters, material quality control, and increasing operator competence.